Comparative Validation Study to Demonstrate the Equivalence of an Alternate Next-Day Enrichment Protocol for VIP® Gold for Salmonella Method to Culture Methods for the Detection of Salmonella in Selected Foods and Environmental Surfaces. (23rd November 2019) - Kerr, David E; Shen, George; Lienau, Andrew H; Kaur, Mandeep; Immermann, Amy L; Feldsine, Philip T; John, Lisa; Chen, Yi; Brodsky, Michael; Ziemer, Wayne
Abstract: Background: VIP ® Gold for Salmonella is a lateral flow immunodetection device that was validated by AOAC in 1999 as Official Method of Analysis 999.09. It was improved upon in 2009 by introducing gold colloid as the detection method. Objective: A simple next-day enrichment protocol using modified enterohemorrhagic Escherichia coli media was developed for the VIP Gold for Salmonella to improve the time-to-results and laboratory work flow. Methods: We tested 128 Salmonella strains, representing all serotypes from A to Z and 51 to 66 as well as 50 non- Salmonella strains for inclusivity/exclusivity. Performance of the VIP using the new enrichment protocol was compared with the U.S. Department of Agriculture (USDA) Microbiology Laboratory Guidebook reference culture procedure for the detection of Salmonella in ready-to-eat poultry, roast beef, and chicken carcass rinsate. VIP performance was also compared with the U.S. Food and Drug Administration (FDA) Bacteriological Analytical Manual (BAM) for the detection of Salmonella from raw spinach, raw almonds, raw pasta, and environmental surfaces (stainless steel, rubber, and plastic). Results: The VIP detected all 128 of Salmonella strains and none of the 50 non- Salmonella strains. There was no statistically significant difference in the numbers of positive results with VIP Gold for Salmonella protocol compared with appropriate USDA-Food Safety and Inspection Service or FDA-BAM reference methods for any of these matrixes. Conclusions: This new enrichment protocol has met all the requirements to be approved as a Performance Tested Method SM . Highlights: The new enrichment protocol will improve the time-to-results and allow quicker decisions about the contamination of food products.